THE EFFECT OF APPARATUS COMPETENCE IN VILLAGE FUND MANAGEMENT AND THE VILLAGE FINANCIAL SYSTEM (SISKEUDES) ON THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT (A SURVEY AT VILLAGE OFFICES THROUGHOUT MASAMA DISTRICT): - Lestari, Ni Komang Sindy; Masdar, Rahma; Din, Muhammad; Meldawati, Lucyani; Betty, Betty (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study aimed to analyze the effect of village fund management officials’ competence and the implementation of the Village Financial System on the accountability of village fund management. The research problem focused on weaknesses in village fund accountability at the village government level. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 70 village officials involved in village fund management. Multiple linear regression analysis was applied to analyze the data. The results show that the competence of village fund management officials has a positive and significant effect on village fund management accountability. In addition, the implementation of the Village Financial System has a positive and significant effect on accountability. Simultaneously, both variables significantly influence village fund management accountability. This study concludes that improving officials’ competence and optimizing the village financial system play an important role in enhancing accountability in village fund management. Keywords: officials’ competence, village financial system, accountability, village funds